Avaliação de impacto sobre a prática docente: um estudo sobre o curso normal superior veredas - Ana Carolina Timo Alves (2008)
The purpose of this research was to evaluate the Normal Superior Veredas, a course aimed to the undergraduate degree of professors from public schools (state and municipal) located in Minas Gerais State. The center of this evaluation was the possible effects of this course on teaching practice. In order to make it, this work raised what competencies were expected within the courses pedagogical purposes and which one of those were effectively developed and practiced by the professors egressed. Two factors were considered: time of experience in teaching activity and duty hours. Possible influences of work conditions and professors profile on the development of the expected competences were also analyzed. Initially, the major normative directives within the field of undergraduate degree for basic education teachers in Brazil were raised from the promulgation of the Law of Directives and Bases of the National Education (Law 9394/96). In the next step, the use of the notion of competencies in the educational speech and especially in professors degree process were analyzed. The accomplished study has established connections between the normative field and the use of its competencies within Normal Superior Veredas pedagogical proposals in the context of regulation. Field research was developed by the creation of focus groups of professors egressed from the course, gathered under the two factors mentioned. The collected data were analyzed considering the foreseen competencies. The conclusion of the study was built based upon the importance that courses that aim to change teaching practice must consider not only professors profile and their works condition, but also the situational regulation that presides works organization in schools.